The Novel Synthesis of CaMnO3 Perovskite Type-Oxide and its Catalytic Activity for Degradation of Dye. (October 2020) - Dewi, N; Setyarini, W; Anggraini, R; Siregar, S S; Awaluddin, A
Abstract: The CaMnO3 perovskite type-oxide has been synthesized using a citrate sol-gel method using two different MnO2 precursors and calcium carbonate. The cryptomelane-type manganese oxide precursor produced well-crystalline CaMnO3 perovskite, whereas pyrolusite-type manganese oxide (commercial) generated mixtures of CaMnO3 perovskite and un-reacted MnO2 using the same CaCO3 as other precursor. The CaCO3 /MnO2 mole ratio seems to play a crucial role to obtain high purity of the CaMnO3 perovskite. The CaMnO3 perovskite proves to have high catalytic activity for the degradation of methylene blue (MB) using hydrogen peroxide as an oxidant. This Fenton catalyst is able to degrade 98.5% of MB within 20 minutes of degradation times at pH 2.